Diagnosis of primary aldosteronism in the hypertension specialist centers in Italy: a national survey. (November 2018) - Pucci, Giacomo; Monticone, Silvia; Agabiti Rosei, Claudia; Balbi, Giulia; Bertacchini, Fabio; Ragazzo, Fabio; Saladini, Francesca; Pengo, Martino
Abstract Primary aldosteronism (PA) is the most common endocrine cause of resistant hypertension. Individuals with PA are at increased cardiovascular risk, and an appropriate management and treatment would ideally reduce such risk. Screening and diagnosis of PA requires a specific diagnostic test which is considered time- and cost-consuming and, as a result, is underperformed in clinical practice. An online survey reviewing available diagnostic procedures, laboratory testing, and clinical protocols for screening and confirmation of PA diagnosis was conducted among clinical lead of Reference and Excellence centers of the Italian Hypertension Society. A total of 102 questionnaires were sent and 62 centers participated in the survey. Assessment of the plasma renin (plasma renin activity/direct renin concentration) and plasma aldosterone concentration (PAC) was available in all centers. Captopril challenge test (CCT) and saline infusion test (SIT) were available in 60% and 61% of the centers, respectively. Fludrocortisone suppression test was available in 32% of the units. Adrenal vein sampling was accessible in 32% of the centers. We found discrepancies in cutoff levels of aldosterone-to-renin ratio (ARR) and PAC after SIT. Other discrepancies involved the duration of the wash-out period before ARR testing and dosage of captopril administered during CCT. In conclusion, although all centers are sufficiently equipped to perform PA screening, often patients should be referred to other centers to confirm the diagnosis of PA. A greater uniformity across centers to define precise cutoffs for screening and confirmatory testing for the diagnosis of PA would be of utility.